Pengaruh Harga Properti Residensial dan Kebijakan Financing to Value Terhadap Stabilitas Perbankan Syariah di Indonesia - Ahmad Fatoni (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze the effect of residential property prices and Financing to Value policies on the stability of Islamic Commercial Banks in Indonesia. This study uses secondary data, namely time series data from all Islamic Commercial Banks in Indonesia during the period March 2010 to December 2020. The model used in this study is the Error Correction Model (ECM). The results of the study found that the Residential Property Price Index of small and medium types in the long term has an influence on the stability of Islamic Commercial Banks. However, each of them supports a different hypothesis, namely the collateral value hypothesis and the deviation hypothesis. Meanwhile, it was found that in the long and short term the Financing to Value policy had an influence on the stability of Islamic Commercial Banks in Indonesia. Keywords: Islamic Banking Stability, Property Price, Financing to Value